Pengesan Optik, Piezoelektrik-fotoakustik - Mat Yunus, W. Mahmood; Talib, Zainal Abidin (Universiti Putra Malaysia Press, 1993)
An optical detector based on piezoelectric detection of the photo acoustic effect in an absorbing metal plate is reported. Such a detector has been used in an experiment for measuring a Gaussian laser beam diameter using the knife-edge method. The responsivity of the detector varied from 4.05J.LV/mW at 68Hz to 1.25J.LV/mW at 211Hz. The Gaussian laser beam diameter obtained from the experimental data is (0.88 ± 0.02)mm and this value is comparable with the value stated in the laser specification note.